Bluetooth Controlled Distribution Board for Circuit Testing in Electrical Wiring Lab - Wan Mohd Faizal, Wan Nik; Sharulnizam, Mohd Mukhtar; Abd Rahman, Mohd Saad, Assoc. Prof. (Malaysian Invention and Design Society (MINDS), 2010)
21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.